Features of physical development of athletes as the basis for differentiation of loads in the training process of young kickboxers - Volodymyr Ashanin; Svitlana Pyatisotska; Yana Zhernovnikova; Andrii Yefremenko; Оlha Beziazychna; Liana Duhina (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to determine the indicators of physical development of athletes of the group of initial training in kickboxing. Material and methods: the research was carried out on the basis of the Children's and Youth Sports School «KIPT», Kharkov. 28 kickboxers of 10-11 years old group of initial training of the first year of study were involved in the experiment. The following research methods were used in the work: theoretical analysis and generalization of scientific literature, anthropometric measurements, methods of mathematical statistics. Results: visual and anthropometric examinations of the athletes' bodies were carried out according to the following indicators: body length and weight, chest circumference. Also, complex testing of athletes' motor qualities was carried out using control exercises provided for by state tests and standards for assessing the physical fitness of the population of Ukraine. Conclusions: in the course of the study, anthropometric examinations of 10-11 years old youths who are engaged in kickboxing were carried out, which made it possible to establish the features of the body structure of athletes body mass and chest height indices were calculated, as well as the Pignet index to determine the somatic type of athletes. As a result of the study, it was revealed that according to the Quetelet index, the overwhelming number of students had a level of physical development of average and higher; according to the index of proportionality of the development of the chest - a narrow chest. According to the revealed value of the Pignet index, it was established that the majority of kickboxers belong to the asthenic type of constitution. The importance of using a differentiated approach in organizing the training process of athletes, taking into account their somatotype, was revealed. Athletes 10-11 years old of different somatotypes (asthenic, normosthenic and hypersthenic) have significant differences in terms of the development of physical qualities. These are the results of the study experimentally confirmed the need to search for new approaches to the system of physical training of athletes taking into account their individual characteristics.